If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 5(8w + -9) = 0 Reorder the terms: 6 + 5(-9 + 8w) = 0 6 + (-9 * 5 + 8w * 5) = 0 6 + (-45 + 40w) = 0 Combine like terms: 6 + -45 = -39 -39 + 40w = 0 Solving -39 + 40w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '39' to each side of the equation. -39 + 39 + 40w = 0 + 39 Combine like terms: -39 + 39 = 0 0 + 40w = 0 + 39 40w = 0 + 39 Combine like terms: 0 + 39 = 39 40w = 39 Divide each side by '40'. w = 0.975 Simplifying w = 0.975
| 36=2L+W | | 1w+5=4 | | 3-2(x-4)=2x-5 | | 3(4x+1)=3+12x-2 | | (X+10)+(4x-20)=90 | | 7R*2+8R+8R= | | 3x(.29)=3 | | 1y+-4x= | | 8v-18=26+3v | | 18+4(-4)= | | 50-40x=200 | | 3t-t=20 | | X^5-2x^4+x^3-x^2+2x-1=0 | | 50+40x=200 | | 5a-2b=8displayngb | | 7+3k-4k=-5-3k | | -5g+1=7+2a | | 2n^3-24n^2-23048=0 | | 2y-4=10x | | 7T+8(7T+2)= | | 4(k+5)=2(9k-2) | | 24xy+6y=0 | | 9n-4n=4n+2n+7 | | 2(8n+6)=-3+n | | 5a-2b=8 | | 3c+2(4)=2 | | 21(7-y)+4=-4 | | 2(x-3)+2X=-14 | | 7-3(5-3v)-8=67 | | 6c=c | | x-6-26=7(x-26) | | Y+7-2=-5 |